Commentary: What should referral pathways have to improve healthcare experiences of women with female genital mutilation in Australia? - Carolyne Njue (BMC, 2021)
Abstract Background We examined the evidence derived from healthcare professionals’ interfacing with women with female genital mutilation (FGM) to comprehend the referral pathways available to these women in Australia. Main body Clinicians encountered FGM-related complications that included ruptured bladder and total urinary incontinence. Midwives and paediatricians indicated a lack of referral pathways for FGM, but used their discretion to refer such cases to social work departments, obstetric/gynaecological units, child protection service providers, psychological counsellors and surgeons. The continuum of care for women with FGM is characterised by inadequate and lack of clear referral pathways. This underscores the need to develop and strengthen referral pathways in response to physical, birthing and psychological complications of women with FGM to improve their care experiences in Australia. Short conclusion Capacity building initiatives on FGM-prevention and care for trainees and practising health providers and community involvement in high burden areas/populations should be implemented to promote uptake and utilization of the referral services. Provision of infrastructural support, including clinical management tools, job aids, posters, referral algorithms and electronic patient records with "drop-down menus" for referral sites for health complications of FGM to reinforce the providers’ efforts are critical.